International Scientific Symposium: Spaces of Memory: Architecture, Heritage, Art. - Vladimir V. Mihajlović (University of Belgrade, 2016)
International Scientific Symposium: Spaces of Memory: Architecture, Heritage, Art. Faculty of Philosophy and Museum of Applied Arts in Belgrade, 12 - 15. 04. 2011